Peranan Badan Permusyawaratan Desa dalam Penyelenggaraan Pemerintahan di Desa - Firman, Firman (Fakultas Hukum, Universitas Muslim Indonesia, 2020)
This study aims to determine and obtain data regarding the implementation of the main tasks and functions of the Village Consultative Body in the administration of government, and obtain data on the factors that influence the implementation of the main tasks and functions of the Village Consultative Body in the administration of government in Mattirowalie Village, Majauleng District, Wajo Regency. The research method uses data collection techniques through, observation, interviews, and documentation. The data obtained from the research results are processed using qualitative analysis to find out and obtain data regarding the implementation of the main tasks and functions of the Village Consultative Body in the administration of government and obtain data on what factors influence the implementation of the main tasks and functions of the Village Consultative Body in the administration of government. The results of this study indicate that the implementation of the main tasks of the BPD in the administration of government has not been fully carried out optimally because only three main tasks are carried out namely accommodating and channelling the aspirations of the community, forming a village head election committee and the process of discussion and stipulation of village regulations together with the village head, out of six the main tasks that have been determined by the Government Regulation on Villages. The factors that influence the implementation of the main tasks and supervisory functions are influenced by two factors, namely the driving factor which includes community support or participation, and a good cooperative relationship between the Village Consultative Body and the Village Government. Whereas the second factor is the inhibiting factor which includes the lack of benefits provided to the members involved, facilities and infrastructure, lack of Human Resources to fill membership and the existence of a society that is either pro or contra to each decision made. Abstract: Penelitian ini bertujuan untuk mengetahui dan memperoleh data mengenai pelakanaan tugas pokok dan fungsi Badan Permusyawaratan Desa dalam penyelenggaraan pemerintahan, dan memperoleh data mengenai faktor-faktor yang mempengaruhi pelaksanaan tugas pokok dan fungsi Badan Permusyawaratan Desa dalam penyelenggaraan pemerintahan di Desa Mattirowalie Kecamatan Majauleng Kabupaten Wajo. Metode penelitian menggunakan teknik pengumpulan data melalui, observasi, wawancara, dan dokumentasi. Data yang telah diperoleh dari hasil penelitian diolah dengan menggunakan analisis kualitatif untuk mengetahui dan memperoleh data mengenai pelakanaan tugas pokok dan fungsi Badan Permusyawaratan Desa dalam penyelenggaraan pemerintahan dan memperoleh data mengenai faktor-faktor apa yang mempengaruhi pelaksanaan tugas pokok dan fungsi Badan Permusyawaratan Desa dalam penyelenggaraan pemerintahan. Hasil penelitian ini menunjukkan bahwa pelaksanaan tugas pokok BPD dalam penyelenggaraan pemerintahan belum sepenuhnya dilakukan secara optimal karena hanya tiga tugas pokok yang dilaksanakan yaitu menampung dan menyalurkan aspirasi masyarakat, membentuk panitia pemilihan kepala Desa dan proses pembahasan dan penetapan peraturan desa bersama dengan kepala desa, dari enam tugas pokok yang telah ditetapkan Peraturan Pemerintah tentang Desa. faktor-faktor yang mempengaruhi pelaksanaan tugas pokok dan fungsi pengawasan dipengaruhi oleh dua faktor yaitu faktor pendorong yang meliputi dukungan atau partisipasi masyarakat, dan hubungan kerjasama yang baik antara Badan Permusyawaratan Desa dengan Pemerintah Desa. Sedangkan faktor yang kedua yaitu faktor penghambat yang meliputi kurangnya tunjangan yang diberikan kepada para anggota yang terlibat, sarana dan prasarana, kurangnya Sumber Daya Manusia yang mengisi keanggotaan serta adanya masyarakat yang pro maupun kontra terhadap setiap keputusan yang ditetapkan.